Services in Eastern Poland - Skąpska, Elżbieta (Regional Barometer. Analyses & Prognoses, 2013)
The development differences in particular regions and sub-regions of the Polish economy have given rise to a need for progress in the scope of services, especially in Eastern Poland, which includes the following voivodships: lubelskie, podkarpackie, podlaskie, świętokrzyskie and warmińsko-mazurskie. The assumed aim of the study is identification of macroeconomic determinants of service sector development, which simultaneously constitute reinforcement of the economic potential of Eastern Poland. It is worth highlighting at least one of the signs of quality transformations in an economic service sector connected with creating new services for business — known as ‘shared services’. The development of outsourcing services will first of all result in producing new jobs, improvement of living standards and increase in wealth of the above-mentioned regional economy.